Metabolic shift precedes the resolution of inflammation in a cohort of patients undergoing bariatric and metabolic surgery - Jose Romeo Villarreal-Calderon (Nature Portfolio, 2021)
Abstract Bariatric and metabolic surgery has shown to promote weight loss and reduce systemic inflammation. However, the sequence and timing of events regarding metabolic improvement and inflammation resolution has been rarely explored. Furthermore, data on inflammatory markers of Th17 and Th1 cell responses after bariatric surgery is scarce. We conducted a prospective study in subjects with obesity that underwent bariatric and metabolic surgery, with follow-ups at 3 and 6 months. Anthropometric and metabolic markers such as insulin levels, HOMA-IR, and lipid parameters declined significantly 3 months after surgery; while hs-CRP, TNF-α, IL-1β, IL-6, and IL-8 serum concentrations decreased 6 months after the procedure. Concentrations of Th1 signature and driver cytokines, particularly IFN-γ, IL-12, and IL-18, and of Th17 driver IL-23 also decreased significantly after 6 months. Significant positive correlations between triglyceride levels and hs-CRP, IL-1β, and IFN-γ concentrations, and between Apo B and IFN-γ levels were observed 6 months after bariatric and metabolic surgery. In addition, BMI was associated with hs-CRP and TNF-α concentrations. Fat mass correlated with hs-CRP, TNF-α, and IL-12. Analysis of the temporality of metabolic and inflammatory events suggests that improvement in the metabolic status occurs before resolution of systemic inflammation and may be a requisite for the later event.